INCREASE OF DURABILITY OF TOOLS MADE OF STEEL R6M5 USED FOR PARTS PRODUCTION IN THE AUTOMOTIVE INDUSTRY - Кhristoforova, T.; Kuzmenko, O.; Христофорова, Т. А.; Кузьменко, Е. А.; Хрістофорова, Т. А.; Кузьменко, О. О. (Харьковский национальный автомобильно-дорожный университет, 2017)
The possibility of improving the durability of stamping and cutting tools made of steel R6M5 (M2) for automotive parts manufacturing is considered. It has been shown that the main factor determining the steel properties is the time of the fist tempering under condition that the modes of quenching and of the second tempering are standard.
ПОВЫШЕНИЕ ДОЛГОВЕЧНОСТИ ИНСТРУМЕНТА ИЗ СТАЛИ Р6М5 ДЛЯ ИЗГОТОВЛЕНИЯ ДЕТАЛЕЙ АВТОМОБИЛЬНОЙ ПРОМЫШЛЕННОСТИ
ПІДВИЩЕННЯ ДОВГОВІЧНОСТІ ІНСТРУМЕНТУ ЗІ СТАЛІ Р6М5 ДЛЯ ВИГОТОВЛЕННЯ ДЕТАЛЕЙ АВТОМОБІЛЬНОЇ ПРОМИСЛОВОСТІ
Keywords: stamping and cutting tools; high-speed steel; tempering; инструмент; быстрорежущая сталь; термообработка; інструмент; швидкорізальна сталь; термообробка; 669.15:621.785.796